2003
DOI: 10.1890/02-8013
|View full text |Cite
|
Sign up to set email alerts
|

How Virulent Should a Parasite Be to Its Vector?

Abstract: Abstract. Vector-borne parasites are commonly predicted to be less virulent to the vector than to the definitive host as the parasite gains little by harming its main route of transmission. Here we assess the empirical evidence from systems in which insects are vectors for vertebrate, plant, and invertebrate parasites. The body of evidence supports lower (but nonzero) parasite virulence to vectors than to plant or invertebrate hosts, but not to vertebrate hosts. We consider why this might be by assessing evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 56 publications
(73 reference statements)
4
54
0
1
Order By: Relevance
“…A primary assumption of research in this area is that evolution should favor effects on vector Þtness which increase transmission (Hurd 2003). Consequently, a commonly held generalization is that evolution should favor pathogens with low virulence toward their insect vectors as the pathogen is dependent on the vector for transmission (Elliot et al 2003). The results presented here support this contention.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A primary assumption of research in this area is that evolution should favor effects on vector Þtness which increase transmission (Hurd 2003). Consequently, a commonly held generalization is that evolution should favor pathogens with low virulence toward their insect vectors as the pathogen is dependent on the vector for transmission (Elliot et al 2003). The results presented here support this contention.…”
Section: Discussionsupporting
confidence: 69%
“…Because studies in this area typically compare the Þtness of vectors reared on infected versus susceptible plants, it is often unclear if Þtness effects are caused by direct effects of the pathogen on the vector or indirect effects caused by changes in host plant quality (Elliot et al 2003). Effects of plant pathogens that do not propagate in vectors are expected to be indirect, whereas effects of plant pathogens that propagate in vectors may be direct or indirect.…”
mentioning
confidence: 99%
“…With varying levels of virulence observed among different vector-pathogen systems, the body of evidence indicates that there is no consistent universal pattern, as, for example, among mosquito-Plasmodium systems (Ferguson & Read 2002). Although it has been suggested that virulence may depend on the relative mobility of the vertebrate host and arthropod vector (Elliot et al 2003), the degree of virulence to a vector and the advantage that it confers to the pathogen remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Effects on the performance of the vector mediated via virus-induced changes in the plant can subsequently have consequences for the success of the pathogen itself. It can be envisaged there will be evolutionary pressures on pathogens to manipulate plant biology so that vector performance is not significantly degraded, and, at best, somehow improved (Castle and Berger 1993;Kluth et al 2002;Eliot et al 2003;Belliure et al 2005). Many investigations into these ''tripartite' ' (or ''trilateral'') plant-insect-virus interactions have demonstrated that aphid growth rate and morphology can be modified when aphids feed on infected plants (e.g.…”
Section: Introductionmentioning
confidence: 99%